Kinerja Ekonomi Usaha Tani Tanaman Pangan dan Kontribusinya pada Kesejahteraan Petani di Desa Sekitar Kawasan Ekonomi Khusus Mandalika, Kabupaten Lombok Tengah - Candra Ayu; Wuryantoro Wuryantoro; Ni Made Wirastika Sari (Institut Pertanian Bogor, 2024)
The Mandalika Special Economic Zone (SEZ) development in West Nusa Tenggara Province aims to accelerate economic growth, especially for people in Pujut District-Central Lombok Regency. This research aims to describe the economic performance of food crop farming in villages around the Mandalika SEZ and its contribution to the economic welfare of farmer households. This research uses descriptive methods, and the data was collected using survey techniques in 3 villages with potential for food crop farming, namely Sengkol, Rembitan, and Sukadana villages. The respondents were 75 farmers. The results showed that food crops in villages around the Mandalika SEZ consist of rice, soybeans, and corn, with low productivity and an R/C ratio of 1.48–2.02. The total income from food crop farming is IDR 7,903,504.28/year or 34.06% of the total household income of farmers. The contribution of food crop farming income to farmer welfare based on the Sajogyo criteria was 41.69%, and based on the World Bank Criteria, it was 18.95%. Keywords: food crop, farmers welfare, farmer household, special economic zone mandalika, Central Lombok